Effect of the growth of anaerobic bacteria on the surface pH of solid media. - Watt, B (1985)
Changes in surface pH occurring after varying periods of anaerobic incubation were measured for a total of 23 test solid media. There was little change in the surface pH of uninoculated plates, but plates inoculated with Bacteriodes fragilis showed a striking fall in pH, to pH 5 in the case of some of the test media. The problems of controlling the surface pH of solid media are discussed and possible methods of control are considered.